Archivist - Gcwadi, Madoda (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
With trembling legs, I descended the stairs. Hoping to hide a sudden weakness I navigated by clinging to the banister for stability. But my legs betrayed me. I collapsed onto the cement stairs. Something was terribly wrong—my heart raced, and fear mingled with a sense of emptiness and confusion. At 13:05 on September 24, 2021, a creepy silence settled over Zisukhanyo High in Samora Machel township. In the days leading up to the incident, I had noticed occasional crunching sensations and a growing weakness in my knees, but couldn't pinpoint the exact cause. Was it due to my continued participation in soccer at the age of 53? I recalled a specific moment after a soccer match when my knees suddenly weakened, making it impossible for me to stand up. Was being a vegetarian contributing to this? A lack of certain nutrients? My genetics? Pulling myself up on the banister, I stumbled and leaned against the wall, then made my way down the quiet corridor toward the administration block swaying my body in an effort to propel my legs forward. Upon reaching the hall where the Grade 12 learners were engrossed in their September trial examination, I mustered a smile and clung to the edge of the nearest desk. Nomtha, a cheerful learner, giggled at my exaggerated movements, while the other learners shook their heads, assuming my Creative Arts subject had taken its toll.